Bilateral central retinal artery occlusion from catastrophic antiphospholipid syndrome. (12th November 2018) - Joshi, Udit; Afroz, Sana; Ranka, Sagar; Mba, Benjamin
Abstract : A 23-year-old woman with history of systemic lupus erythematous presented with dizziness and headache and was admitted for the stroke workup. During her stay, she had sudden painless loss of vision in her right eye consistent with central retinal artery occlusion (CRAO). Ocular massage and paracentesis were attempted without success to resume the flow. She was started on oral high-dose steroids (1 mg/kg) for lupus flare and therapeutic anticoagulation for antiphospholipid syndrome (positive for anticardiolipin and beta-2 microglobulin antibodies). On day 4, she started having painful bluish discoloration of her left index finger and right fifth toe, and on day 5 she had acute onset of left blurry vision with findings consistent with CRAO. She fulfilled the criteria of catastrophic antiphospholipid syndrome and was started on intravenous pulse steroids, plasmapheresis and higher international normalised ratio goal of 3–3.5 with improvement in her left eye vision from 20/200 to 20/20 on near card test by the end of treatment.